The relationship between BMI and maternal weight gain during pregnancy with birth weight - Somayeh Moeindarbari; Toktam Forghani; Fatemeh Rezaei Sharif (Mashhad University of Medical Sciences, 2022)
Introduction: Various factors, such as proper nutrition of the mother, affect the health of the mother and fetus. Weight gain of the mother during pregnancy is one of the valid criteria to evaluate her nutritional status. Considering that low birth weight babies are more at risk of death due to their special conditions, the present study was conducted aimed to investigate the relationship between BMI and maternal weight gain during pregnancy with neonates' birth weight.Methods: In this retrospective cohort study, the information of all babies born in Fariman city in 2020 (n=2026) along with their mothers was collected through the Sina's electronic health record  (Nutrition review form and breastfeeding consultation form, newborn care form and prenatal care form) and an organized interview, demographic information and weight, birth height, weight, mother's height at the beginning of pregnancy and at the end of pregnancy, mother's BMI, type of delivery, and pregnancy history were collected. Data were analyzed by SPSS statistical software (version 22) and Chi-square, Fisher and Mann-Whitney tests. P<0.05 was considered statistically significant.Results: There was a significant relationship between mother's BMI, chronic disease, number of mother's pregnancies, number of care provided during pregnancy, use of prenatal supplements, gestational age, type of delivery, multiple births and baby's gender with low birth weight babies (p<0.05). Also, there was a significant difference in mother's BMI, mother's weight at the beginning of pregnancy, weight at the end of pregnancy, and baby's height in two groups of low birth weight and normal weight babies (P<0.05).Conclusion: The mother's BMI at the beginning of pregnancy and weight at the end of pregnancy can affect the birth weight of the baby, therefore, it is necessary to pay attention to this issue and increasing the level of awareness of the employees of health-medical centers and women of reproductive age.